Redroot pigweed interference with lettuce crop - Casadei, Eloisa [UNESP]; Bacha, Allan L. [UNESP]; Rodrigues, Juliana S.; Santos, Renata T. S. [UNESP]; Alves, Pedro L. C. A. [UNESP]; Filho, Arthur B. C. [UNESP] (Univ Federal Vicosa, 2020)
Background: Lettuce-production areas in Brazil are frequently infested by pigweed plants, which can interfere with production by competing for resources or releasing allelopathic compounds in the environment. Objective: The present study evaluated the effect of redroot pigweed (Amaranthus retroflexus) density and distribution on lettuce crop (Lactuca sativa L.). Methods: The cultivars Lidia, Veronica, Lucy Brown and Salad Bowl were used. After transplanting, these plants coexisted until harvest with four pigweed plants (equivalent to 16 plants m(-2)) located within or outside planting rows, or with one pigweed plant located at the center of the plot (4 plants m-2), as well as a control without weed. The experiment was conducted in an open and semi-controlled area, with treatments arranged in a 4x4 factorial scheme, in a completely randomized experimental design with three replicates. Evaluations included: the number of leaves, fresh matter (lettuce only), height, leaf area and dry matter of lettuce and redroot pigweed plants. Results: The coexistence with redroot pigweed caused yield losses of up to 45% for cultivar Lidia; 41% for Salad Bowl; 33% for Veronica; and 28% for Lucy Brown. Conclusions: The density of 16 plants m(-2) of redroot pigweed was the one that most negatively affected the growth of the cultivars, in which the positioning in the planting lines resulted in greater interference to the crop growth. Among the cultivars tested, Lucy Brown showed greater tolerance to coexistence with redroot pigweed plants, while the cultivar Lidia was the most sensitive to the imposed interference.
Keywords: Lactuca sativa L.; Amaranthus retroflexus; competition; weeds; density; distribution